Intoxications and their meanings - Reinarman, Craig (Routledge handbook of intoxicants and intoxication, 2023)
“Intoxication” is a word that warrants interrogation. Its essence is taken to be an altered state of consciousness, but altered compared to what? The root word “toxic” is misleading as there are common varieties of intoxication that fall well short of being poisoned and others that involve no “toxin” or psychoactive substance at all. Despite the ubiquity of intoxication, its boundaries are blurry; the behaviors grouped under it are historically and culturally specific. Some intoxicants are socially approved, while others are feared and punished, and these meanings change over time (e.g., alcohol, tobacco, and cannabis). If it is not the mere fact of altered consciousness that defines intoxication, then we need to attend to the conditions under which altered states get defined as troubling or not troubling, which often depends on who is intoxicated, by what means, when, and where. This chapter attempts to tease out some core themes that cut across the shifting moral careers of common intoxicants and to situate them in the broader currents of social change. Intoxicants have become technologies of the modern self that make us increasingly aware that present consciousness is but one state of consciousness among many.